Challenges of in situ hybridization in miRNA analysis of triple-negative breast cancer morphological diversity - Kolečková, Markéta; Bezděková, Michala; Bouchal, Jan; Janíková, Mária; Bohošová, Júlia; Slabý, Ondřej; Svoboda, Marek; Srovnal, Josef; Vomáčková, Katherine; Überall, Ivo; Kolář, Zdeněk (Neoplasma, 2023)
miRNA expression in triple-negative breast cancers (TNBC) has mainly been studied from a methodological viewpoint. However, it has not been considered that miRNA expression profile may be associated with a specific morphological entity inside every tumor. The verification of this hypothesis on a set of 25 TNBCs was the subject of our previous work, where we confirmed specific expression of the studied miRNAs in 82 samples of different morphologies including inflammatory infiltrate, spindle cell, clear cell, and metastases after RNA extraction and purification as well as microchip and biostatistical analysis. In the current work, we demonstrate a low suitability of in situ hybridization method for miRNA detection compared to RT-qPCR, and in detail discuss the biological role of 8 miRNAs with the most significant changes of expression.